The thief [compact disc, unabridged] : an Isaac Bell adventure - Cussler, Clive (Cussler, Clive. Isaac Bell novels, 2012)
On the ocean liner Mauretania, two European scientists with a dramatic new invention are barely rescued from abduction by the Van Dorn Detective Agency's intrepid chief investigator, Isaac Bell. Unfortunately, they are not so lucky the second time. The thugs attack again-and this time one of the scientists dies. What are they holding that is so precious? Only something that will revolutionize business and popular culture-and perhaps something more. For war clouds are looming, and a ruthless espionage agent has spotted a priceless opportunity to give the Germans an edge. It is up to Isaac Bell to figure out who he is, what he is up to, and stop him.